THE CENTRAL CHARACTER’S SOCIAL BACKGROUND AND ITS RELATION TO DOMESTIC CONFLICT IN KEVIN KWAN’S RICH PEOPLE PROBLEM - Aristi, Sri Nida; Ratih P, Shita Dewi; Widisanti, Ni Made (Universitas Pakuan, 2023)
The thesis entitled